2016
DOI: 10.1080/02699052.2016.1187289
|View full text |Cite
|
Sign up to set email alerts
|

ICU sedation with dexmedetomidine after severe traumatic brain injury

Abstract: Objective To comprehensively describe the use of dexmedetomidine in a single institutional series of adult ICU patients with severe TBI. We describe the dexmedetomidine dosage and infusion times, as well as the physiological parameters, neurological status, and daily narcotic requirements before, during, and after dexmedetomidine infusion. Methods We identified 85 adult patients with severe TBI who received dexmedetomidine infusions in the Trauma ICU at Vanderbilt University Medical Center between 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…Widely used in the intensive care unit to alleviate pain and anxiety, maintain the stability of hemodynamics, with less respiratory depression without requirement for mechanical ventilation, easy to wake patients up to judge the consciousness state, can be used as a preventive drug for PSH in TBI patients (66,80,81).…”
Section: Advantagesmentioning
confidence: 99%
“…Widely used in the intensive care unit to alleviate pain and anxiety, maintain the stability of hemodynamics, with less respiratory depression without requirement for mechanical ventilation, easy to wake patients up to judge the consciousness state, can be used as a preventive drug for PSH in TBI patients (66,80,81).…”
Section: Advantagesmentioning
confidence: 99%
“…Through its action on the α2 receptor in the spinal cord, dexmedetomidine can produce an analgesic effect and lead to the sedation and anxiety remission. It is a strong sedative and does not affect the patient’s sense of judgment, making dexmedetomidine an ideal sedative for patients with severe craniocerebral injury in perioperative period [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…While not as extensively studied as beta-blockers in TBI, proponents of the LC point to multiple preclinical TBI studies that showed neuroprotective effects and decreases in plasma catecholamine levels with the use of alpha-2 agonists [56,57]. Furthermore, there is recent clinical evidence that dexmedetomidine is safe in patients with severe TBI and may decrease requirements for narcotics and additional sedatives [58].…”
Section: Anti Hypertensive Therapymentioning
confidence: 99%